Availability of primary care team members can improve teamwork and readiness for change. Issue 4 (October 2016) - Rodriguez, Hector P.; Chen, Xiao; Martinez, Ana E.; Friedberg, Mark W.
Abstract : Background: Early experiences of patient-centered medical home implementation indicate that redesigning primary care is an intensive organizational change that is most effectively undertaken by high-functioning interdisciplinary teams. Team effectiveness research indicates that consistent availability of team members and other aspects of team structure can impact teamwork and organizational outcomes. Methods: We conducted a survey of 766 adult primary care providers and staff in 34 California safety net practices to assess primary care team structure (team size, team member availability, and access to interdisciplinary expertise), teamwork, and readiness for change. We used path models with robust standard errors for clustering of respondents within practices to examine relationships between team member availability and readiness for change. Using path analysis, we examined the extent to which better teamwork mediated relationships between team member availability and readiness for change. Results: We received 628 completed surveys (response rate = 82%). Greater team member availability was associated with greater readiness for change, but the relationship was stronger for staff than for primary care providers. Contrary to our hypothesis, path analyses revealed that the relationship of team member availability and greater readiness for change was only partially mediated (21%) by better teamwork. The direct effect of teamwork on readiness for change is approximately 2.9 times larger than the direct effect of team member availability on greater readiness for change. Conclusions: Ensuring that members perceive that their teammates are routinely available to them may improve readiness for implementing organizational changes like adopting patient-centered medical home models. Given that better teamwork only partially explained the availability–readiness relationship, additional research to identify the mechanisms through which consistent team member availability increases change readiness could lend insight into how to more effectively support clinicians and staff undergoing complex organizational changes.